Development of Fisherman Groups in the Central Fisheries Development Area, Sape District, Bima Regency - Arman, Arman; Junaidin, Junaidin; Lutfi, Muhamad; Hendra, Hendra; Ardiansyah, Nike; Ardyansah, Ady (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Community Service Activities entitled